Innovative Blood Antioxidant Test in Standardbred Trotter Horses - Raffaella Rossi; Chiara Maria Lo Feudo; Enrica Zucca; Francesco Vizzarri; Carlo Corino; Francesco Ferrucci (MDPI AG, 2021)
In athletic horses, prolonged and intense training gives rise to an imbalance between the production of free radicals and antioxidant molecules, leading to oxidative stress. Considering the relation between exercise and oxidative stress in horses, the present work aims to validate the Kit Radicaux Libres (KRL) test as a tool to verify the influence of taming, training and racing on the total blood antioxidant activity and some haematochemical parameters. Five Italian Standardbred racehorses (two males and three females, aged 12 ± 1 months) from the same training center were selected and monitored upon arrival and during the following year until the racing season. Blood samples were obtained at different timepoints, corresponding to different steps of training. The data showed that KRL values were higher (p < 0.001) before the beginning of the taming period and at 60 days of taming, compared with the training and racing periods; additionally, the total protein value was affected by the training program, whereas no effects of training on muscle enzymes were detected. These results confirm that exercise plays a role in the production of free radicals and show that the KRL test may represent a valid method to determine oxidative stress in athletic horses.